Information literacy skill: An alternative to support biology student’s learning outcomes - Saptasari, Murni; Sunarmi, S.; Sulasmi, Eko Sri; Wicaksono, Rido Sigit; Sudrajat, Ahmad Kamal (University of Muhammadiyah Malang, 2019)
Information literacy is a fundamental aspect to ease students in encompassing the knowledge-making process as well as empowering their capacity in using and creating various information and knowledge products. The purpose of this study was to determine the effect of integrating information literacy rubric with Project-Based Learning on students? learning outcomes in Structure of Plant Development course. This quasi-experimental research used a non-randomized pretest-posttest control group design. The population in this study was the all biology department undergraduate students at the Universitas Negeri Malang in 2018/2019 academic year. The sample consisted of 120 students which were divided into two groups (control and experiment). The data gained was analyzed using one-way ANCOVA. The results showed that Project-Based Learning which was integrated with information literacy rubric had a significant impact on biology students? learning outcomes. Based on the findings, it is suggested that educators should provide a proper strategy as an effort to support their students? learning outcomes.